L’écologie en plus. Des justifications environnementales de la non-procréation - Clarisse Veaux; Sébastien Roux (VertigO, 2023)
The “ecological crisis” would revolutionize our reproductive behavior. Alerted by the non-sustainability of a supposed overpopulation or concerned about a future announced as apocalyptic, more and more individuals would choose to renounce procreation and would refrain from having children, out of ethical concern. Based on a recent study among a young generation of childfree individuals, we show how environmental concerns are indeed influencing some family arrangement choices. However, our interviews also demonstrate that the ecology, if present, is a secondary ethical argument that legitimizes - or even ennobles – a previous desire for a childfree life. By giving voice to the arguments of those individuals, notably women, who choose not to have children for ecological reasons, the article shows that their concern, less than a shared trend, is in fact inscribed in a singular context where the will not to procreate remains tainted by a powerful stigma, calling for justification and avoidance strategies.